2023
DOI: 10.3390/en16093639
|View full text |Cite
|
Sign up to set email alerts
|

Development of Surface Mining 4.0 in Terms of Technological Shock in Energy Transition: A Review

Abstract: The expansion of end-to-end Industry 4.0 technologies in various industries has caused a technological shock in the mineral resource sector, wherein itsdigital maturity is lower than in the manufacturing sector. As a result of the shock, the productivity and profitability of raw materials extraction has begun to lag behind the industries of its deep processing, which, in the conditions of volatile raw materials markets, can provoke sectoral crises. The diffusion of Industry 4.0 technologies in the mining secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 153 publications
0
1
0
Order By: Relevance
“…The article by S. Zhironkin and E. Taran [13] considers the diffusion of the end-to-end technologies of Industry 4.0 in the sector of fossil energy production in the context of shocks and fluctuations in the mineral resource market that accompanies the energy transition. The authors identified the main domain areas of Surface Mining 4.0: neural networks and artificial intelligence, Big Data and cloud computing, Internet of Things, digital twins, blockchain, machine vision and learning (including unmanned equipment), smart sensors, drones, and 3D visualization.…”
mentioning
confidence: 99%
“…The article by S. Zhironkin and E. Taran [13] considers the diffusion of the end-to-end technologies of Industry 4.0 in the sector of fossil energy production in the context of shocks and fluctuations in the mineral resource market that accompanies the energy transition. The authors identified the main domain areas of Surface Mining 4.0: neural networks and artificial intelligence, Big Data and cloud computing, Internet of Things, digital twins, blockchain, machine vision and learning (including unmanned equipment), smart sensors, drones, and 3D visualization.…”
mentioning
confidence: 99%